Synthesis and characterization of biopolymers obtained from epoxidized linseed oil using polythiols as cross-linking agents - Santos, Fernanda Barreto dos [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The search for more sustainable alternatives for industrial production has been intensified in light of current environmental challenges. The increasing demand for energy and products, combined with the depletion of natural resources, has driven research into new raw materials and less polluting processes. In this context, vegetable oils are considered a promising renewable source for obtaining biopolymers. The versatility of the triglyceride chains present in vegetable oils allows various functional groups to be incorporated, enabling the synthesis of materials with specific properties. In this study, the synthesis and characterization of new renewable polymers from the epoxy-thiol reaction were investigated. A monomer was synthesized through an epoxidation reaction using linseed oil as a raw material, resulting in epoxidized linseed oil. The obtained monomer was characterized using spectroscopic and thermal techniques, with thermal stability of 108.2 °C being observed due to the incorporation of epoxy groups into the triglyceride chain. For polymerization via the epoxy-thiol reaction, the catalysts DABCO and TBAB were tested (using the monomer and the polythiol 3,6-dioxa-1,8-octanedithiol), with TBAB being identified as the most effective catalyst for the analyzed systems. From the synthesized monomer, polymerization was carried out using the polythiols 1,3,4-thiadiazole-2,5-dithiol, 3,6-dioxa-1,8-octanedithiol, and pentaerythritol tetrakis(3-mercaptopropionate) as crosslinkers. The polymerization temperature and time were determined based on results obtained through Differential Scanning Calorimetry. The obtained polymers exhibited thermal stability above 170 °C, as well as luminescent properties and variations in coloration, along with different physical and chemical properties. Whenever possible, the epoxidation and polymerization reactions were optimized. The starting materials, monomer, and synthesized polymeric materials were characterized using analytical techniques such as titration, Simultaneous Differential Thermal Analysis (TG-DTA), Differential Scanning Calorimetry (DSC), Nuclear Magnetic Resonance Spectroscopy (¹H-NMR), and Fourier Transform Infrared Spectroscopy (FTIR). The results obtained demonstrate the potential of linseed oil for the synthesis of biopolymers with adjustable properties, contributing to the development of new sustainable materials.

A busca por alternativas mais sustentáveis para a produção industrial tem sido intensificada diante dos desafios ambientais atuais. A crescente demanda por energia e produtos, associada ao esgotamento de recursos naturais, tem impulsionado a pesquisa por novas matérias-primas e processos menos poluentes. Nesse contexto, os óleos vegetais são considerados uma promissora fonte renovável para a obtenção de biopolímeros. A versatilidade das cadeias triglicerídeas presentes nos óleos vegetais permite que diversos grupos funcionais sejam incorporados, possibilitando a síntese de materiais com propriedades específicas. Neste trabalho, a síntese e caracterização de novos polímeros renováveis a partir da reação epóxi-tiol foram investigadas. Um monômero foi sintetizado pela reação de epoxidação, utilizando-se o óleo de linhaça como matéria-prima, resultando no óleo de linhaça epoxidado. O monômero obtido foi caracterizado por técnicas espectroscópicas e térmicas, sendo observada uma estabilidade térmica de 108,2 °C devido à incorporação dos grupos epóxidos à cadeia triglicerídea. Para a polimerização pela reação epóxi-tiol, os catalisadores DABCO e TBAB foram testados (utilizando-se o monômero e o politiol 3,6-dioxa-1,8-octanoditiol), sendo o TBAB definido como o melhor catalisador para os sistemas analisados. A partir do monômero sintetizado, a polimerização foi realizada utilizando-se como intercruzantes os politióis 1,3,4-tiadiazol-2,5-ditiol, 3,6-dioxa-1,8-octanoditiol e pentaeritritol tetraquis(3-mercaptopropionato). A temperatura e o tempo de polimerização foram determinados a partir dos resultados obtidos por meio da técnica de Calorimetria Exploratória Diferencial. Os polímeros obtidos apresentaram estabilidade térmica superior a 170 °C, além de propriedades luminescentes e variações em coloração, bem como em propriedades físicas e químicas. Sempre que possível, as reações de epoxidação e polimerização foram otimizadas. Os materiais de partida, o monômero e os polímeros sintetizados foram caracterizados por meio de técnicas analíticas, incluindo titulação, Análise Térmica Diferencial Simultânea (TG-DTA), Calorimetria Exploratória Diferencial (DSC), espectroscopia por ressonância magnética nuclear (¹H-RMN) e espectroscopia vibracional de absorção no infravermelho médio (FTIR). Os resultados obtidos demonstram o potencial do óleo de linhaça para a síntese de biopolímeros com propriedades ajustáveis, contribuindo para o desenvolvimento de novos materiais sustentáveis.
Síntese e caracterização de biopolímeros obtidos a partir de óleo de linhaça epoxidado utilizando politióis como agentes intercruzantes
Keywords: Polymers; Vegetable oils; Thiol-epoxy; Green chemistry; Polímeros; Oleos vegetais; Tiol-epóxi; Química verde